2019
DOI: 10.1101/739144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sirolimus plus nintedanib treats vascular pathology in HHT mouse models

Abstract: Hereditary hemorrhagic telangiectasia (HHT), a genetic bleeding disorder leading to systemic arteriovenous malformations (AVMs), is caused by loss-of-function mutations in the ALK1-ENG-Smad1/5/8 pathway. Evidence suggests that HHT pathogenesis strongly relies on overactivated PI3K-Akt-mTOR and VEGFR2 pathways in endothelial cells (ECs). In the BMP9/10immunoblocked (BMP9/10ib) neonatal mouse model of HHT, we report here that the mTOR inhibitor, sirolimus, and the receptor tyrosine-kinase inhibitor, nintedanib, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…We and others have previously reported that BMP9/10-Alk1 signaling mechanistically links flow sensing and VEGFR2-PI3K/AKT pathway activation 12-15, 17, 20, 50 . Alk1 signaling counteracted both flow and growth factor-induced AKT activation, and the absence of Alk1 overactivated PI3K/AKT signaling in AVMs [51][52][53] . We extend these findings here by demonstrating that ALK1 is required for flow-induced PI3K-AKT polarization against the direction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that BMP9/10-Alk1 signaling mechanistically links flow sensing and VEGFR2-PI3K/AKT pathway activation 12-15, 17, 20, 50 . Alk1 signaling counteracted both flow and growth factor-induced AKT activation, and the absence of Alk1 overactivated PI3K/AKT signaling in AVMs [51][52][53] . We extend these findings here by demonstrating that ALK1 is required for flow-induced PI3K-AKT polarization against the direction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Various therapeutic approaches targeting Alk1 are under investigation, including monoclonal antibodies, small molecule inhibitors, and gene therapy to modulate Alk1 expression and signaling [69,119]. Ruiz et al found that Sirolimus and nintedanib in combination prevented vascular pathology in the oral mucosa, lungs and liver of the BMP9/BMP10immunoblocked mice [120]. Sirolimus binds FKBP12 and inhibits mTOR downstream of PI3K and AKT.…”
Section: Modulation Of Bmp9-10/eng/alk1/smad Pathway As An Emerging T...mentioning
confidence: 99%
“…Ruiz et al found that Sirolimus and nintedanib in combination prevented vascular pathology in the oral mucosa, lungs and liver of the BMP9/BMP10-immunoblocked mice [120]. Tacrolimus is a strong activator of the BMP9/ALK1/Smad signaling cascade and it has been used for treatment of animal HHT and decreased the development of retinal AVMs [71].…”
Section: Modulation Of Bmp9-10/eng/alk1/smad Pathway As An Emerging T...mentioning
confidence: 99%